Recidivism in a Sample of Serious Adolescent Offenders - Brame, Robert (J Quant Criminol, 2016)
OBJECTIVES: A broad research literature in criminology documents key aspects of how criminal offending develops and changes over the life span. We contribute to this literature by showcasing methods that are useful for studying medium-term patterns of subsequent criminal justice system involvement among a sample of serious adolescent offenders making the transition to early adulthood. METHODS: Our approach relies on 7 years of post-enrollment follow-up from the Pathways to Desistance Study. Each person in the study was adjudicated delinquent for or convicted of one or more relatively serious offenses during adolescence. Their local jurisdiction juvenile court petition records and their adult FBI arrest records were systematically searched. RESULTS: We estimate in-sample 7-year recidivism rates in the 75% to 80% range. Our analysis also provides recidivism rate estimates among different demographic groups within the sample. Extrapolated long-term recidivism rates are estimated to be on the order of 79% to 89%. CONCLUSIONS: The Pathways data suggest that recidivism rates of serious adolescent offenders are high and quite comparable to the rates estimated on other samples of serious offenders in the extant literature. Our analysis also reveals a pattern of heightened recidivism risk during the earliest months and years of the follow-up period followed by a steep decline.